2004
DOI: 10.1038/sj.jhh.1001809
|View full text |Cite
|
Sign up to set email alerts
|

Associations between plasma antioxidants and hypertension in a community-based sample of 415 Australians aged 60–64

Abstract: It has been suggested that increased oxidative stress may be both a cause as well as a consequence of hypertension. In vivo oxidation of low-density lipoproteins by oxygen-free radicals may increase hypertension-related atherogenesis, and antioxidants may be beneficial in this regard. Previous findings concerning associations between serum measures of antioxidants and hypertension have however been inconsistent. Plasma levels of b-carotene, Vitamin A, E, uric acid, homocysteine and total antioxidant capacity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 37 publications
2
25
0
2
Order By: Relevance
“…Oxidative stress may result from an excessive production of ROS or a reduced antioxidant availability. In this light, it has been described that in hypertensive patients, the plasma levels of antioxidants, such as vitamins A and E, and total antioxidant capacity are decreased [3]. Alterations of normal endothelium function appear to play a central role in the pathogenesis of hypertension [4].…”
Section: Introductionmentioning
confidence: 98%
“…Oxidative stress may result from an excessive production of ROS or a reduced antioxidant availability. In this light, it has been described that in hypertensive patients, the plasma levels of antioxidants, such as vitamins A and E, and total antioxidant capacity are decreased [3]. Alterations of normal endothelium function appear to play a central role in the pathogenesis of hypertension [4].…”
Section: Introductionmentioning
confidence: 98%
“…However, the SU.VI.MAX trial found no reduction in incident BP after 6.5 years of supplementation with a combination of purified antioxidant vitamins and minerals,14 Thus, it is plausible that serum carotenoids, which might play an antioxidant role or be a marker of a generally healthy diet and lifestyle, relate inversely to future BP increase. However, only a few cross-sectional studies4,15,16 and one prospective study14 have reported an inverse relation between serum carotenoids and hypertension. Therefore, we conducted longitudinal analyses to clarify whether serum carotenoid concentrations measured at 3 different examinations predict incident hypertension in the Coronary Artery Risk Development in Young Adults (CARDIA) study.…”
mentioning
confidence: 99%
“…14) MDA is a major and stable end product formed during the peroxidation of lipids and is regarded as marker of lipid peroxidation in tissues. 15) Here, we reported that Rb1 antagonizes H 2 O 2 -induced HUVECs senescence through upregulating endogenous antioxidants SOD and decreasing vascular lipid peroxidation. Cell Culture Primary HUVECs were prepared from newborn human umbilical cords within 6 h by 0.1% collagenase (Gibco) perfusion as described previously.…”
mentioning
confidence: 99%